2015
DOI: 10.1097/acm.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

Junior Doctors’ Views of How Their Undergraduate Clinical Electives in Palliative Care Influenced Their Current Practice of Medicine

Abstract: Findings suggest that junior doctors trained earlier in palliative care have enhanced competencies of professionalism, patient-centered medicine, psychosocial and spiritual aspects of palliative care, communication, teamwork, and self-awareness. Learning a palliative approach can help them make a difference in treating dying patients, but also in general patient care. Therefore, physicians trained in palliative care may be better prepared to contribute to a health care system that is person-centered, ethically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
1
32
0
4
Order By: Relevance
“…A formal assessment of the learning needs of the students, especially after their first contacts with dying patients, might be helpful for further development of the curriculum. Our results are in line with previous studies showing that education in PM is appreciated by medical students as well as by physicians [2527]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A formal assessment of the learning needs of the students, especially after their first contacts with dying patients, might be helpful for further development of the curriculum. Our results are in line with previous studies showing that education in PM is appreciated by medical students as well as by physicians [2527]. …”
Section: Discussionsupporting
confidence: 93%
“…A recent study by Gerlach et al showed that a course consisting of seven times 90-minute classes in palliative care increased medical students’ self-confidence concerning somatic, spiritual and psychological aspects of PM and resulted in high knowledge in a post-course test [24]. Education in PM may also help to adapt patient-centered care in general [25]. However, most of these studies have concentrated on the short term effects of a single course of PM education [20, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies concluded that previous training in PC increases the competencies of trainees with end-of-life care 20,21 and general patient care. 41 Two thirds of the trainees surveyed agreed that mandatory rotations in PC should be implemented in medical schools and residency training programs. Most oncology fellowships across the nation do not have mandatory rotations in PC.…”
Section: Discussionmentioning
confidence: 99%
“…35 42 Senior support is variable and specialty-dependent, 12 17 22 38 42 with most support being practical advice rather than emotional. 17 Senior support is particularly lacking when senior doctors had limited experience of caring for frail older patients or greater experience in medical or surgical interventions. 37 38 40 41 Junior doctors report receiving support outside the medical team, from nursing colleagues, 22 27 35 40 41 47 palliative care specialists, 12 18 22 25 40 friends and family, 17 39 and online advice.…”
Section: Thrown In At the Deep Endmentioning
confidence: 99%
“…12 40 41 Palliative care rotations, at postgraduate or undergraduate level, are seen as the best way to achieve this 12 15 20-22 25 28 because the rotations or placements are valued as opportunities to address the unmet needs from medical school, which included specific and transferable skills in symptom control, professionalism, teamwork, communication, reflective practice 17 20 21 25 37 44 and in ethical-legal framework. 17 There was one exception where junior doctors reported hospice placements as medically deskilling experiences, but this had a low weight of evidence. 20 Other learning methods valued by junior doctors include observation of senior colleagues 14 17 21 31 37 40 43 49 and reflection in clinical contexts 14 17 24 40 41 or social settings.…”
Section: Addressing the Gapmentioning
confidence: 99%